2013
DOI: 10.1089/dna.2012.1951
|View full text |Cite
|
Sign up to set email alerts
|

Renin Angiotensin System Blockage Associates with Insertion/Deletion Polymorphism of Angiotensin-Converting Enzyme in Patients with Hypertensive Emergency

Abstract: Hypertensive crisis (HC) stands out as a form of acute elevation of blood pressure (BP). It can manifest itself as hypertensive emergency (HE) or hypertensive urgency (HU), which is usually accompanied with levels of diastolic BP ≥120 mmHg. Angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism may influence manifestations of HC. Thus, this study evaluated the influence of ACE I/D polymorphism in individuals with HC. A total of 187 patients admitted with HC (HU [n=69] and HE [n=118]) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Established link has already been demonstrated between ACE I/D polymorphism and the risk of myocardial infarction and cardiovascular events (Hamelin et al, 2011;Vaisi-Raygani et al, 2010;Zintzaras et al, 2008), microalbuminuria (Pontremoli et al, 2000;Staessen et al, 1997), left ventricular hypertrophy (Perticone et al, 1997), thoracic aortic aneurysm in patients with bicuspid or tricuspid aortic valves (Foffa et al, 2012), pregnancy hypertensive disorders (Chen et al, 2012;Reshetnikiv et al, 2015), and hypertensive emergency (Vilela-Martin et al, 2013). Yet, the findings of this study are in line with the above-mentioned investigations.…”
Section: Discussionmentioning
confidence: 96%
“…Established link has already been demonstrated between ACE I/D polymorphism and the risk of myocardial infarction and cardiovascular events (Hamelin et al, 2011;Vaisi-Raygani et al, 2010;Zintzaras et al, 2008), microalbuminuria (Pontremoli et al, 2000;Staessen et al, 1997), left ventricular hypertrophy (Perticone et al, 1997), thoracic aortic aneurysm in patients with bicuspid or tricuspid aortic valves (Foffa et al, 2012), pregnancy hypertensive disorders (Chen et al, 2012;Reshetnikiv et al, 2015), and hypertensive emergency (Vilela-Martin et al, 2013). Yet, the findings of this study are in line with the above-mentioned investigations.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, another investigation demonstrated individuals presented with emergency hypertensive (HE) characterized by TOD had a lower frequency of the II genotype and less use of RAS blockers when compared with the hypertensive urgency group, characterized as no TOD. Thus, the risk of an individual having HE was increased in the presence of these two conditions (low frequency of the II genotype and less use of RAS blockers) [ 18 ]. On the other hand, one study demonstrated the effect of ramipril in inflammatory response in patients undergoing coronary artery bypass grafts without the ACE I/D gene polymorphism influence [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ACE I/D polymorphism is linked to risk for myocardial infarction and cardiovascular events [ 6 9 ], LVH [ 10 12 ], microalbuminuria [ 11 , 13 , 14 ], thoracic aortic aneurysm in patients with bicuspid or tricuspid aortic valves [ 15 ], pregnancy hypertensive disorders [ 16 , 17 ], and hypertensive emergency [ 18 ]. Moreover, this polymorphism is related to inter-individual differences in BP response, for example, a low dose of the hydrochlorothiazide diuretic produced greater BP reductions in men with the DD genotype and women with the II genotype [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pressão arterial média dos participantes foi diferente entre os estudos incluídos. A média de PAS / PAD foi mais alta em um estudo realizado no Brasil relatando um nível de PA de 201,0 (± 29,3) / 128,1 (± 18,0) (VILELA- MARTIN et al, 2013). E a média de PAS/PAD foi mais baixa em um estudo indiano que relatou um nível de PA de 145,5 (± 14,05) / 93,6 (± 8,09) (SRIVASTAVA et al, 2012).…”
Section: Meta-análiseunclassified